2005
DOI: 10.1111/j.1467-9957.2005.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Licensing Contract in a Stackelberg Model*

Abstract: We study optimal linear licensing and its social welfare implications when the innovator (patentee) is an insider that can make capacity/output commitment so as to act as a Stackelberg leader in the output market. We show that (i) the patentee's profit-maximizing licensing contract is a royalty; (ii) the optimal royalty rate is greater than the cost reduction attained by the licensed technology and is increasing in the number of competitors; (iii) optimal licensing maximizes the likelihood of technology transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 12 publications
2
34
2
Order By: Relevance
“…This literature started by Tauman (1984, 1986) and Shapiro (1985, 1986) who analyzed licensing in standard oligopoly models. Later studies expanded the analysis by considering general two-part tariff policies (Sen and Tauman 2007), models with differentiated goods (Muto 1993, Faulí-Oller andSandonís 2002), asymmetric information (Gallini andWright 1990, Beggs 1992), incumbent innovators (Shapiro 1985, Marjit 1990, Wang 1998, Kamien and Tauman 2002, strategic delegation (Mukherjee 2001, Saracho 2002, Stackelberg leadership (Kabiraj 2004, Filippini 2005, moral hazard (Choi 2001), or the integer problem (Sen 2005), etc.…”
Section: Introductionmentioning
confidence: 99%
“…This literature started by Tauman (1984, 1986) and Shapiro (1985, 1986) who analyzed licensing in standard oligopoly models. Later studies expanded the analysis by considering general two-part tariff policies (Sen and Tauman 2007), models with differentiated goods (Muto 1993, Faulí-Oller andSandonís 2002), asymmetric information (Gallini andWright 1990, Beggs 1992), incumbent innovators (Shapiro 1985, Marjit 1990, Wang 1998, Kamien and Tauman 2002, strategic delegation (Mukherjee 2001, Saracho 2002, Stackelberg leadership (Kabiraj 2004, Filippini 2005, moral hazard (Choi 2001), or the integer problem (Sen 2005), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing licensing by means of upfront fees (which may be collected via an auction) and royalties, the early literature concluded that licensing by means of upfront fees dominates royalty licensing for an outside innovator (Kamien & Tauman, 1984;Kamien & Tauman, 1986;Kamien, et al, 1992). As royalties are frequently observed in practice, the conclusion on the suboptimality of royalty licensing generated a number of papers that argued that royalties can be explained by factors, such as informational asymmetry (Gallini & Wright, 1990;Rockett, 1990;Sen, 2005a), product differentiation (Muto, 1993;Wang & Yang, 1999;Poddar & Sinha, 2004), leadership structure (Kabiraj, 2004;Kabiraj, 2005;Filippini, 2005), or by the fact that the number of licenses must be an integer (Sen, 2005b). There is a small literature that considers issues of international trade in the context of technology transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Kamien and Tauman (1986) shows that if the licensor lacks production capacity, a fixed fee is better than a royalty, and is also better for consumers. This topic is addressed under Stackelberg oligopoly both when a licensor has production capacity (Wang and Yang (2004); Kabiraj (2005);Filippini (2005)) and when it lacks production capacity (Kabiraj (2004)). La Manna (1993) analyzes a Cournot oligopoly with a fixed fee under cost asymmetry, and shows that if technologies can be replicated perfectly, a lower-cost firm always has an incentive to transfer its technology.…”
Section: Related Literaturementioning
confidence: 99%